Ultrabright Lanthanide Nanoparticles. Issue 6 (16th February 2016) - Goetz, Joan; Nonat, Aline; Diallo, Abdoulaye; Sy, Mohamadou; Sera, Ildan; Lecointre, Alexandre; Lefevre, Christophe; Chan, Chi Fai; Wong, Ka‐Leung; Charbonnière, Loïc J.
Abstract: Tb‐doped La0.9 Tb0.1 F3 nanoparticles were prepared by a simple and reproducible microwave‐assisted synthetic protocol in water. The nanoparticles were characterized by XRD, TEM, dynamic light scattering and inductively coupled plasma atomic emission spectroscopy elemental analysis. Eleven ligands with varying coordination and photosensitizing abilities were designed to bind at the surface of the Tb‐doped nanoparticles. The photosensitizing behavior was monitored by electronic absorption spectroscopy and steady‐state and time‐resolved emission spectroscopy. The two most effective photosensitizing ligands were used to isolate and purify the capped nanoparticles. The composition and spectroscopic properties of these nanoparticles were measured, which revealed either 2660 and 5240 ligands per nanoparticle, molar absorptivities of 7.6×10 6 and 1.6×10 7 m −1 cm −1 and luminescence quantum yields of 0.29 and 0.13 in water, respectively. These data correspond to exceptional brightness values of 2.2×10 6 and 2.1×10 6 m −1 cm −1, respectively. The as‐prepared nanoparticles were imaged in HeLa cells by fluorescence microscopy, which showed their specific localization in lysosomes. Abstract : Put your coat on : Eleven ligands were tested for surface photosensitization of Tb‐doped LaF3 nanoparticles. Isolation, purification and characterization of the surface‐coated nanoparticles led to extremely bright scaffolds (brightness >10 6 m −1 cm −1 ) that are stable in the presence of large excesses of competing anions. The nanoparticles were shown by luminescence microscopy to internalize into HeLa cells and localize to the lysosomes.